ANALISIS TINGKAT KESADARAN MAHASISWA TERHADAP PENTINGNYA SERTIFIKASI PROFESI - Mila Viendyasari (Jurnal Administrasi Bisnis Terapan, 2019)
The long-term goal of this research is to be useful for stakeholders at the University of Indonesia and help the University of Indonesia Professional Certification Institute. The first target is specifically for this research to be an input for Certification Bodies and University of Indonesia lecturers to always improve socialization regarding the importance of professional certification. Secondly, so that students are more aware of the importance of professional certification. The method used in this study is descriptive analysis method, which is a method that aims to provide an overview of an object of research under study through collected samples or data and make generally accepted conclusions. The sample of this study is the UI Vocational Program students from 11 Study Programs.